Effects of Cheonwangbosim-dan in a Mouse Model of Chronic Obstructive Pulmonary Disease: Anti-Inflammatory and Anti-Fibrotic Therapy - Jee Hyun Kang; Eunhye Jung; Eun-Ju Hong; Eun Bok Baek; Mee-Young Lee; Hyo-Jung Kwun (Applied Sciences, 2023)
Chronic obstructive pulmonary disease (COPD) is a lung illness, marked by dyspnea, coughing, and sputum production. Cheonwangbosim-dan (CBD) is a traditional East Asian medicine, consisting of a combination of 15 medicinal herbs, which is frequently used to treat arterial/auricular flutter, neuroses, cardiac-malfunction-induced diseases, and insomnia. The present study evaluated the therapeutic effect of CBD (100 or 200 mg/kg) on COPD using a mouse model of COPD induced by cigarette smoke (CS) and lipopolysaccharide (LPS). The increase in inflammatory cell numbers caused by exposure to CS and LPS was significantly reduced by CBD administration. In addition, CBD therapy reduced interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in bronchoalveolar lavage fluid (BALF). In lung tissue, CBD not only reduced the levels of IL-1β (CBD 100: p < 0.001 and CBD 200: p < 0.001), IL-6 (CBD 100: p < 0.001 and CBD 200: p < 0.001), TNF-α (CBD 100: p = 0.005 and CBD 200: p = 0.014), and monocyte chemoattractant protein-1 (MCP-1; CBD 100: p = 0.018 and CBD 200: p = 0.003), but also decreased the expression of α-smooth muscle actin (α-SMA; CBD 100: p < 0.001 and CBD 200: p < 0.001), transforming growth factor-β (TGF-β; CBD 100: p < 0.001 and CBD 200: p < 0.001), matrix metallopeptidase-7 (MMP-7; CBD 100: p = 0.019 and CBD 200: p < 0.001), MMP-9 (CBD 100: p = 0.015 and CBD 200: p = 0.013), and tissue inhibitor of metalloproteinase-1 (TIMP-1; CBD 100: p = 0.035 and CBD 200: p = 0.013) compared with the COPD group. CBD was also found to suppress the phosphorylation of nuclear factor kappa B (NF-κB), extracellular signal-regulated kinase 1/2 (ERK1/2), and p38 mitogen-activated protein kinases (p38 MAPK). Taken together, these findings showed that CBD can attenuate respiratory inflammation and airway remodeling induced by exposure to CS and LPS, suggesting that CBD has probable preventive and therapeutic applications in patients with COPD.